Small-Signal Stability Analysis of the Power System Based on Active Support of Renewable Energy VSCs - Chu, Tianfeng; Xu, Miao; Xie, Yu; Wang, Shunjiang; Li, Dianyang; Liu, Gang (Frontiers in Energy Research, 2022)
With the large-scale renewable energy access to the power system, the voltage source converters (VSCs) in the system are gradually increasing. The system inertia is weakened, which leads to the decrease in frequency supportability and affects the stability of the power system. After adopting active support control, VSC-based renewable energy units have inertia supportability similar to traditional synchronous generators (SGs), which can improve the frequency stability of the power system. This article is intended to the control strategy based on active support of renewable energy. Small-signal stability of a two-zone system with different control strategies for VSCs under different conditions is analyzed. At the same time, the dynamic adjustment effect of different parameters on active support control is considered, and frequency stability of a two-zone system with inertial flexible control is improved. In this article, the basic principle of active support control is expounded in detail. Compared with PQ-control and droop-control, it is verified that active support control has good frequency supportability. The small-signal model of VSCs for active support and two-machine system is established. Combined with the simulation system, the influence of virtual inertia and damping coefficient on system stability is verified.